PELATIHAN PENGGUNAAN OFFICE EXCEL KEPADA REKAN-REKAN DINAS BAPPEDA LOMBOK TENGAH - maulida, nurul; hamdi, saeful; Saikin; mutawalli, Lalu (CV. Aksara Global Akademia, 2025)
Indonesia has experienced significant technological advances, including in the field of computer technology. This requires the government to adapt to changing technological developments. Therefore, Microsoft Excel training has been conducted for Central Lombok Bappeda employees to increase their knowledge and understanding of formulas that can facilitate the use of Microsoft Excel office applications. This training was held by the Monev division and aims to improve the ability of Bappeda employees to process data in a professional manner. It is hoped that this training will assist employees in completing tasks and meeting the needs of the Bappeda agency effectively.